2014
DOI: 10.1155/2014/876158
|View full text |Cite
|
Sign up to set email alerts
|

On the Fresh/Hardened Properties of Cement Composites Incorporating Rubber Particles from Recycled Tires

Abstract: This study investigates the ameliorative effects on some properties of cement-based materials which can be obtained by incorporating rubber particles as part of the fine aggregates. The aim is to find out optimal cement composite/mortar mixtures, containing recycled-tyre rubber particles, suitable for specific engineering applications. Different percentages of rubber particles, from 0% to 75%, were used and, for each percentage, the suitable amount of sand was investigated in order to achieve the best fresh/ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…From the early research works [6], it was clear that substituting natural aggregates by rubber particles has led to a significant drop in the compressive strength. Subsequent investigations [7][8][9] confirmed earlier findings and highlighted the improved damping properties of rubberized concrete [10][11][12]. e optimization of the rubberized concrete mix, although a complex task, may lead to high-value applications from the point of view of sustainability [13].…”
Section: Introductionmentioning
confidence: 69%
“…From the early research works [6], it was clear that substituting natural aggregates by rubber particles has led to a significant drop in the compressive strength. Subsequent investigations [7][8][9] confirmed earlier findings and highlighted the improved damping properties of rubberized concrete [10][11][12]. e optimization of the rubberized concrete mix, although a complex task, may lead to high-value applications from the point of view of sustainability [13].…”
Section: Introductionmentioning
confidence: 69%
“…Several previous studies indicated that the use of rubber tire crumbs reduced mechanical characteristics of concrete/mortar. [20][21][22][23][24][25][26] It should be noted, however, that the compressive strength of brick masonry walls is not only influenced by the strength of the mortar but also limited by the strength of the brick. Sometimes the addition of mortar strength no longer gives significant changes to the compressive strength of brick masonry walls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the use of rubber tire crumbs reduced the compressive, tensile and flexural strengths. [20][21][22][23][24][25][26] Increasing the amount of the rubber crumb will result in further decrease in strength properties. The strength reduction is attributed to the weak bonding between the rubber particles and the cement matrix.…”
Section: Mechanical Characteristicsmentioning
confidence: 99%
“…This is attributed to the thermal conductivity of the materials, which are lower than that of cement. Fiore et al [60] found that the inclusion of 10% by volume, of fine rubber aggregate results in a 23% improvement of thermal insulation. These studies have shown that rubberised concrete containing either chipped or crumb rubber particles exhibit has a lower thermal conductivity when compared to plain concrete.…”
Section: Thermal Conductivitymentioning
confidence: 99%